Effect of Store Atmosphere and Location on Buying Interest - Eltie Christi Sandag; Ashur Harmadi; I Wayan Gede Antok Setiawan Jodi; Pandu Adi Cakranegara; Teguh Setiawan Wibowo (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze effect of store atmosphere and location on buying interest. This research uses descriptive and quantitative research methods. The population taken in this study are all visitors who are interested in buying products and services offered at the Medan Unique Market Store. The number of customers who shop at the Medan Unique Market Store cannot be known and confirmed, so this is one of the reasons for using this method due to time constraints and this method is more efficient. The sample in the study is set at 100 respondents. The analytical tool in this study is multiple linear regression. The results show that store atmosphere has a positive and insignificant effect on buying interest. Location has a positive and insignificant effect on buying interest.